PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PT. SURACO JAYA ABADI MOTOR CABANG ANTANG MAKASSAR - Muhammad Amir (Jurnal Bisnis dan Kewirausahaan, 2017)
The purpose of this study is intended to determine the effect of marketing mix namely product, price, promotion and distribution of consumer purchasing decisions at PT. Suraco Jaya Abadi Motor Branch Antang Makassar. The research was conducted at PT. Suraco Jaya Abadi Motor Branch Antang Makassar. Data collection methods used in this study is primary data which is the data directly taken from the object of research by using observation and questionnaires filled by respondents ie consumers PT. Suraco Jaya Abadi Motor Branch Antang Makassar. The analytical methods used to solve the problems and prove the hypothesis include the analysis of index numbers, validity test, reliability test, multiple linear regression analysis and hypothesis testing that includes t test, F test, and coefficient of determination (R2). The results concluded that the marketing mix of product, price, promotion and distribution influence consumer purchasing decisions at PT. Suraco Jaya Abadi Motor Branch Antang Makassar. Based on the results of the calculation Test coefficient of determination (R2) can be seen that the coefficient of determination (R2) obtained by 0.446. This means that 44.60% of purchasing decision variables can be explained by variations of product variables, price, promotion and distribution, while 55.40% is explained by other variables not found in this study.